Fourier‐transform infrared spectroscopy of biofluids: A practical approach. Issue 2 (24th January 2021) - Theakstone, Ashton G.; Rinaldi, Christopher; Butler, Holly J.; Cameron, James M.; Confield, Lily Rose; Rutherford, Samantha H.; Sala, Alexandra; Sangamnerkar, Sayali; Baker, Matthew J.
Abstract: Biofluid spectroscopy is an emerging technology in the field of clinical investigation, providing a simple way to extract diagnostic and observational information from easy to acquire samples. Infrared spectroscopy is well suited to analyse a large range of biofluid samples, including blood and its derivatives, due to flexible sampling modes and high sensitivity to subtle biological changes. As the technology advances towards the clinic, factors influencing successful clinical translation are becoming apparent. Here, we provide a tutorial for effective biofluid spectroscopy study design, discussing sample and instrument parameters, as well as clinical considerations. The aim is to present the current understanding of clinical translation in the field of biofluid spectroscopy, and to facilitate other clinical applications to advance to the clinic. Abstract : Biofluid spectroscopy allows for a rapid and non‐destructive analysis, providing an emerging technology in the field of clinical investigation. Combined with advanced chemometrics interpretation of complex biological materials is achieved. Effective study design, sample and instrument parameters, and data analysis is vital for clinical translation.